Determination of 7Be, 210Pb and 22Na Activity in Air and Rainwater samples by Gamma-ray Spectroscopy - Savva, M.; Anagnostakis, M. (HNPS Advances in Nuclear Physics, 2019)
The activity concentration of cosmogenic radionuclides in atmospheric aerosol has been used in many applications, such as air mass transport models and solar activity reconstructions. One of the most studied cosmogenic radionuclides is 7Be which is being monitored at the Nuclear Engineering Department of the National Technical University of Athens (NED- NTUA) since many years, with high accuracy and precision. Sodium-22 is another cosmogenic radionuclide met in such studies, however less reported due to its very low activity concentration, of the order of 1 μBq/m3 [1], [2] – roughly four orders of magnitude lower than that of 7Be. Besides cosmogenic radionuclides, radionuclides of terrestrial origin like the 222Rn progeny 210Pb are also used in atmospheric aerosol studies. Lead-210 serves as an ideal tracer of continental air masses because 222Rn emission from oceans and lakes is negligible (<1%) compared to land sources. However, its deposition exhibits geographic and seasonal variations depending on 226Ra content of the top soils, soil-porosity and meteorology of a particular region [3]. Values reported for 210Pb activity in the air range from 0.1 to 3.4 mBq/m3 [4]. During this research, an investigation regarding the detection of 210Pb and 22Na in atmospheric aerosol and the determination of 7Be/22Na ratio has been conducted at NED-NTUA. Sampling and analysis methods were appropriately selected to allow for the detection of all three nuclides in aerosol samples. In order to study the role of precipitation in surface air 7Be, 210Pb and 22Na activity concentration, a procedure for collecting and analyzing rainwater was also developed. From the results obtained so far it is concluded that with the sampling and analysis procedures followed, 210Pb can be easily determined with reasonable accuracy. As far as 22Na is concerned, it was concluded that it can be detected although with high uncertainty, since its activity concentration is within the limits of detection.